Constraints on the Northwestern Atlantic deep water circulation from 231Pa/230Th during the last 30,000 years - Süfke, Finn; Pöppelmeier, Frerk; Koutsodendris, Andreas; Blaser, Patrick; Lippold, Jörg (Paleoceanography and paleoclimatology, 2019)
Four new 231Pa/230Th records form a depth transect in the northwestern Atlantic in millennial‐scale resolution back to 30 ka - Combined records resolve millennial‐scale deep water variabilities like ...
First published: 11 November 2019
Im Titel ist "231" bei Pa und "230" bei Th hochgestellt
Gesehen am 18.01.2021